Penerapan IoT pada Alat Temperature Monitoring System Cold Chain Box Vaccine Menggunakan Sensor DS18B20 - Putra, Akmal Darman; Defit, Sarjon; Nurcahyo, Gunadi Widi (Universitas Putra Indonesia YPTK Padang, 2025)
Unit Pelaksana Teknis (UPTD) Farmasi Dinas Kesehatan Kabupaten Siak Office Pharmacy is fully responsible for maintaining the quality of the vaccine until the vaccine is distributed, the process of storing vaccines in the cold chain box has a problem, namely, it is not equipped with a real-time temperature monitoring device that can provide a warning to pharmacists if the cold chain box temperature rises due to internal or external damage. In addition to the problems mentioned, there is another problem, namely the temperature recording process is still done manually every 2 hours on the log sheet by pharmacists. Based on this, the purpose of this study is to develop technological innovation in the pharmaceutical field, namely by creating an IoT-based temperature monitoring tool that is integrated with the Telegram application and the Blynk IoT application. The research methods used in this study are the waterfall method, experiments, and UML modeling. The process of running this system begins when the sensor is inserted into the cold chain box then the sensor will send temperature data to the Blynk IoT application to be displayed in real-time. The performance of this technology works with the provision that if the temperature does not comply with the provisions, a warning will appear on the Blynk IoT and Telegram applications, the temperature data is then saved and will be used as a basis for making a report by the pharmacist. This research produces a temperature monitoring device using a DS18B20 temperature sensor and an ESP8266 microcontroller with an accuracy rate of more than 95% and this system can also provide real-time temperature data information and warnings via telegram. This research is expected to contribute to the pharmaceutical field as well as the benefits and convenience for pharmacists in monitoring temperature and recording temperature data